Tumor-associated macrophages as major source of APRIL in gastric MALT lymphoma - Munari, Fabio; Lonardi, Silvia; Cassatella, Marco A; Doglioni, Claudio; Cangi, Maria Giulia; Amedei, Amedeo; Facchetti, Fabio; Eishi, Yoshinobu; Rugge, Massimo; Fassan, Matteo; de Bernard, Marina; D'Elios, Mario M; et al. (Blood, 2011)
Lymphoid hyperplasia of gastric mucosa associated with Helicobacter pylori (HP) infection represents a preneoplastic condition of the mucosa associated lymphoid tissue (MALT), which may evolve to a B-cell lymphoma. While it is well established that the initial neoplastic proliferation of B cells is antigen-driven and dependent on the helper activity of HP-specific T cells, it needs to be elucidated which cytokine or soluble factor(s) promote B-cell activation and lymphomagenesis. Herein, we originally report that gastric MALT lymphoma express high levels of a proliferation inducing ligand (APRIL), a novel cytokine crucial in sustaining B-cell proliferation. By immunohistochemistry, we demonstrate that APRIL is produced almost exclusively by gastric lymphoma-infiltrating macrophages located in close proximity to neoplastic B cells. We also show that macrophages produce APRIL on direct stimulation with both HP and HP-specific T cells. Collectively, our results represent the first evidence for an involvement of APRIL in gastric MALT lymphoma development in HP-infected patients.